Underactive Bladder - Chapple, Christopher R.; Wein, Alan J.; Osman, Nadir I. (Springer International Publishing : Imprint: Springer, 2017)
In this book, the authors look at the field of underactive bladder and its presentation, clinical diagnosis, potential etiopathogenesis and treatment. While the editors address a great deal of background information, they clearly identify that many limitations still exist to clinical diagnosis and urodynamic evaluation, and in particular a dearth of appropriate treatment options. This complex condition needs to be recognized and identified in the routine evaluation and clinical management of patients.
Keywords: Medicine.; Rectum -- Surgery.; Urology.; elektronické knihy; electronic books